THE ANALYSIS OF QUALITY TRANSLATION OF "BANDUNG YELLOW PAGES POCKET TRAVEL SERIES" (JANUARY - JUNE 2008 EDITION) - P Saptarini, - (2009)
This paper presents an analysis of the quality translation in BANDUNG YELLOW PAGES POCKET TRAVEL SERIES. It analyzes the quality of the translation viewed from accuracy, clarity and naturalness aspects and the common problems encountered in the translation. This study employs a descriptive qualitative method.. In the process of analyzing the data, there were some steps conducted by the writer. The first step was selecting the sentences that would be analyzed by using random sampling proposed by Fraenkel and Wallen. Then, those samples given to the respondents to be analyzed to find its quality and some commons problem encountered in the translation. Finally, the data were obtained from the respondents was analyzed by using Barnwell and Larsons' theory to reveal the quality and common problems in the translation. The findings of the research show that the quality of Bandung Yellow Pages Travel Series Edition belongs to fair category and there are some common problems that encountered in the translation such diction, addition, omission, grammatical errors and deviation of meaning.